Results of the 2021 French National Perinatal Survey and trends in perinatal health in metropolitan France since 1995 - Le Ray, Camille; Lelong, Nathalie; Cinelli, Hélène; Blondel, Béatrice; Le Ray, Camille; Lelong, Nathalie; Cinelli, Hélène; Blondel, Béatrice; Regnault, Nolwenn; Demiguel, Virginie; Lebreton, Elodie; Salanave, Benoit; et al. (Journal of gynecology obstetrics and human reproduction, 2022)
•The 2021 ENP survey complement the data supplied by routine information systems about maternal characteristics, preventive behaviors and medical practices.•Maternal obesity rate continued to increase significantly.•Some preventive behaviors are improved such as a decrease in tobacco use during pregnancy between 2016 and 2021.•In 2021, induction of labor was more frequent, and concerned one quarter of women in France.•Medical interventions during labor significantly decreased: artificial rupture of membranes, oxytocin use and episiotomy.•Exclusive breastfeeding increased very slightly between 2016 and 2021, and concerned a little more than half of women in postpartum wards. To report results of the 2021 French National Perinatal Survey (ENP) in metropolitan France and assess trends in the main indicators of perinatal health, medical practices, and risk factors in France since 1995. All the samples included all women giving birth at a gestational age of at least 22 weeks of gestation and/or to an infant weighing at least 500 grams in all maternity units in metropolitan France during one week in 1995 (N=13 048), 2003 (N=14 324), 2010 (N=14 546), 2016 (N=12 553), and 2021 (N=12 088). The data came from postpartum interviews of the women at the hospital and their medical records. Comparisons between surveys showed trends over time. Between 1995 and 2021, maternal characteristics changed. Maternal age and the frequency of women with obesity rose: in 2021, 24.6% of women were 35 years or older (21.1% in 2016, 19.2% in 2010, 15.9% in 2003 and 12.4% in 1995) and 14.4% were obese (11.8% in 2016, 9.9% in 2010 and 7.4% in 2003). Some antenatal prevention behaviors that improved in 2021 were not smoking during the third trimester, acid folic administration before pregnancy, and vaccination against influenza. The percentage of women with an early prenatal appointment (“4th month appointment”), implemented to facilitate screening of maternal vulnerability during pregnancy, has continued to rise. The percentage of women receiving prenatal care by midwives has risen markedly (39.0% in 2021 versus 11.7% in 2016). Serum screening for Down syndrome continues to increase (91.8% of women in 2021). The rate of induction of labor has risen significantly (20.2% in 1995 and 25.8% in 2021). The mode of delivery has not varied significantly since 2003; in 2021, the cesarean rate was 21.4% and the instrumental vaginal delivery rate 12.4%. Episiotomy was increasingly rare, among both primiparous and multiparous women (16.5% and 2.9% in 2021, respectively). The prevalence of coronavirus (SARS-CoV2) infection during pregnancy was 5.7%. Preterm live births increased regularly, slightly but significantly over the 1995-2016 period and then remained stable between 2016 and 2021 (7.0%). In 2021, 56.3% of women exclusively breastfed during their hospital stay, a modest increase in comparison with 2016 (54.6%). Routine national perinatal surveys highlight positive trends over time in some preventive practices, decreases in some medical interventions consistent with national guidelines, and the increasing role of midwives in prenatal care. Nonetheless, some indicators remain less than optimal and require more detailed analyses.